2011
DOI: 10.1128/mcb.05668-11
|View full text |Cite
|
Sign up to set email alerts
|

IRE1-Dependent Activation of AMPK in Response to Nitric Oxide

Abstract: While there can be detrimental consequences of nitric oxide production at pathological concentrations, eukaryotic cells have evolved protective mechanisms to defend themselves against this damage. The unfoldedprotein response (UPR), activated by misfolded proteins and oxidative stress, is one adaptive mechanism that is employed to protect cells from stress. Nitric oxide is a potent activator of AMP-activated protein kinase (AMPK), and AMPK participates in the cellular defense against nitric oxide-mediated dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 65 publications
(92 reference statements)
3
60
0
Order By: Relevance
“…Another study showed that quercetin activated AMPK by AMP-dependent and AMP-independent mechanisms [47]. Additionally, quercetin has been shown to activate AMPK via activation of reactive oxygen species generation and inositol-requiring enzyme 1α (IRE1α) RNase [48,49]. The present data also show that PMQ can activate AMPK.…”
Section: Discussionsupporting
confidence: 67%
“…Another study showed that quercetin activated AMPK by AMP-dependent and AMP-independent mechanisms [47]. Additionally, quercetin has been shown to activate AMPK via activation of reactive oxygen species generation and inositol-requiring enzyme 1α (IRE1α) RNase [48,49]. The present data also show that PMQ can activate AMPK.…”
Section: Discussionsupporting
confidence: 67%
“…For example, a recent study showed that the RNase activity of IRE1␣ may be required for nitric oxide-mediated activation of AMPK (53), whereas UPR activation down-regulates the mTOR pathway to enhance autophagy, presumably to provide amino acids by degradation of unnecessary proteins (54). Conversely, AMPK activation reduces translation and attenuates ER stress and UPR (34 -39), similar to our observation.…”
Section: Discussionmentioning
confidence: 99%
“…1A) The RNase activity of IRE1 is required for B. abortus infection induced-AMPK activation. IRE1 has been reported to play an important role in mediating AMPK activation in response to ER stress (18). In addition, Brucella intracellular survival can trigger ER stress in host cells (13)(14)(15).…”
Section: B Abortus Infection Induces Ampk Activation In Hela Cellsmentioning
confidence: 99%
“…IRE1, which has been identified to be a necessary protein for B. abortus replication (17), is both a kinase and an endoribonuclease. ER stress is able to induce IRE1-dependent AMPK activation in response to nitric oxide (18). However, the role of IRE1 RNase in mediating AMPK activation during B. abortus infection remains unclear.…”
mentioning
confidence: 99%